Women’s Empowerment through Indonesian Conditional Cash Transfer (CCT): Program Keluarga Harapan (PKH) - Widia Lestari, Drajat Tri Kartono, Argyo Demartoto (International Journal of Advanced Science and Technology, 2020)
This research aims to explain the role of Indonesian Conditional Cash Transfer (CCT): Program Keluarga Harapan (PKH) in creating women’s empowerment in Sukoharjo Regency, Central Java, Indonesia. This study is a qualitative research with case study approach. Informants are selected using purposive sampling technique. This study takes 24 informants, consisting of main informants, key informants, and supporting informants. Data collection methods used in this study are observation, interview, and documentation. Data analysis techniques used consist of three stages: data reduction, data display, and conclusion drawing. Data verification was conducted in persistent observation with source and time triangulation. The results of this study show that PKH is Conditional Cash Transfer (CCT) aiming to improve the poor’s access to education and health. Moreover, PKH is also a pro-women’s empowerment program. There are also some sub-programs in PKH; joint business group (Kelompok Usaha Bersama or KUBE), FDS (Family Development Session), and Cooperative which have big contributions to improve the household economy. The role of PKH in empowerment can improve women’s welfare, access, awareness, and participation in the field of education, social, and economy. However, PKH has not reached control level of empowerment yet as the highest level in Longwe’s women’s empowerment framework. Women’s empowerment through PKH is a strategic and productive action to maintain the poor’s economic resilience toward independence.